Price-related consumer discussions in China and the United States: a cross-cultural study investigating price perceptions and word-of-mouth transmission - Sebastian Schneider (Journal of Revenue and Pricing Management, 2021)
Prices are among the most frequently discussed topics in consumer research. Although word-of-mouth is known to be highly influential and it is considered to be of growing importance, previous research has largely neglected price-related word-of-mouth, especially in a cross-cultural context. The present study fills this research gap by analyzing the effects of price-related word-of-mouth valence, price changes communicated by word-of-mouth, market mavenism and national culture on price fairness and expensiveness perceptions, as well as on subsequent word-of-mouth intentions. Two studies employing Hofstede's national culture dimensions reveal considerable differences between the cultures of the United States and China.
Keywords: 330; Pricing; Word-of-mouth; Price perception; Transmission; Cross-cultural comparison